2021
DOI: 10.3390/w13081084
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Carbamazepine onto Modified Zeolitic Tuff in Different Water Matrices: Batch and Continuous Flow Experiments

Abstract: Carbamazepine (CBZ) is the most frequently detected pharmaceutical residues in aquatic environments effluent by wastewater treatment plants. Batch and column experiments were conducted to evaluate the removal of CBZ from ultra-pure water and wastewater treatment plant (WWTP) effluent using raw zeolitic tuff (RZT) and surfactant modified zeolite (SMZ). Point zero net charge (pHpzc), X-ray diffraction (XRD), X-ray fluorescence (XRF), and Fourier Transform Infrared (FTIR) were investigated for adsorbents to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…[31] In addition to the above studies, which considered hydrophobic high-silica zeolites, other authors have investigated CBZ adsorption in cation-exchanged FAU-type zeolites having an intermediate Si/Al ratio of 2.8, [36] and onto pristine and surfactant-modified zeolite-rich tuffs. [37] Rather low CBZ uptakes were reported in both cases.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…[31] In addition to the above studies, which considered hydrophobic high-silica zeolites, other authors have investigated CBZ adsorption in cation-exchanged FAU-type zeolites having an intermediate Si/Al ratio of 2.8, [36] and onto pristine and surfactant-modified zeolite-rich tuffs. [37] Rather low CBZ uptakes were reported in both cases.…”
Section: Introductionmentioning
confidence: 87%
“…Besides studies of individual zeolites, granular composite materials consisting of crystallites of different zeolites (high‐silica BEA, MFI, and MOR) held together by a clay‐based binder have also been considered [31] . In addition to the above studies, which considered hydrophobic high‐silica zeolites, other authors have investigated CBZ adsorption in cation‐exchanged FAU‐type zeolites having an intermediate Si/Al ratio of 2.8, [36] and onto pristine and surfactant‐modified zeolite‐rich tuffs [37] . Rather low CBZ uptakes were reported in both cases.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published on surfactant-modified zeolites as organic [38,39] and inorganic [37,40,41] toxicants adsorbents. Several studies [40][41][42][43] suggested that among the many surfactants, the hexadecyl-trimethylammonium bromide (HDTMA) is the most widely applied as an agent that can enhance the ability of zeolites to adsorb the organic pollutants by increasing zeolite hydrophobicity. In more recently published studies, Fuss et al [44] investigated the chemical (acid, basic) and thermal methods for zeolite activation regarding the capacity of natural zeolites to adsorb the odors and toxic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above studies, which considered hydrophobic high-silica zeolites, other authors have investigated CBZ adsorption in cation-exchanged FAU-type zeolites having an intermediate Si/Al ratio of 2.8, 33 and onto pristine and surfactant-modified zeolite-rich tuffs. 34 Rather low CBZ uptakes were reported in both cases.…”
Section: Introductionmentioning
confidence: 87%